2014
DOI: 10.5851/kosfa.2014.34.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Shelf Life for Butter and Cheese Products in Actual and Accelerated Conditions

Abstract: The aim of this study was to estimate the shelf life of butter and cheese products, with shelf life being a guide used to determine the storage period of food before deterioration. Butter and cheese samples stored at 10℃ and 15℃ had a shelf life of 221 d, while those stored at 25℃ and 35℃ had a shelf life of 109 d. Quality changes, including total cell count, coliform counts, Listeria monocytogenes counts, acid value, moisture content, pH, acidity and overall sensory evaluation, were monitored. In order to pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…The variation might be drained of the moisture from butter. Park et al [23] also reported similar variations in their study. The changes (p<0.05) in the pH during the refrigerated storage (7 °C) of butter are presented in Table II.…”
Section: B Physicochemical Attributes Of Butter During Storagesupporting
confidence: 77%
“…The variation might be drained of the moisture from butter. Park et al [23] also reported similar variations in their study. The changes (p<0.05) in the pH during the refrigerated storage (7 °C) of butter are presented in Table II.…”
Section: B Physicochemical Attributes Of Butter During Storagesupporting
confidence: 77%
“…However, butter churned at 10 °C contains more solid fat facilitating incorporation of more water in the butter .matrix, when compared to butter churned at 22 °C. Churning at low temperature (TL) and TLW results in butter with an average water droplet size at day 5 of 5.5 mm, while commercial butter had an average diameter of 2.8mm [43]. An increase in the churning temperature from 10 to 22 °C leads to a significant increase in water droplet size, with an average value of 18.5mm, corresponding to a decreased SFC.…”
Section: Buttermentioning
confidence: 99%
“…To develop a predictive model to quantify the shelf life of yoghurt with FEO, a mathematical model was developed (Mataragas et al ). Park et al () have used the Arrhenius equation to calculate the shelf lives of butter and cheese according to physiochemical (pH and acidity), microbiological (coliforms, bacteria and Listeria monocytogenes ) and sensory experimental data. Titratable acidity (TA) and total coliform bacteria (TCB) of yoghurt were considered as critical parameters in determining the shelf life of a product with respect to its physicochemical and microbial properties (Zhi et al ).…”
Section: Resultsmentioning
confidence: 99%